Clinical research in speech and hearing - Joseph L Stewart (Journal of All India Institute of Speech and Hearing, 1970)
A review of the history of research in speech pathology and audiology as it has been conducted in the United States is both interesting and perplexing; interesting,  because it shows a great deal of sophistication and scientific rigor for a field so young, and perplexing  because  as it has shown strength through growth, the growth has been away from clinical research in favour of more basic research.   To the extent that funds for research, through the Government, eventually determine the course of research the direction back to clinical problems has already begun.